Comparative study of abdominal cavity temporary closure techniques for damage control - RIBEIRO JR,MARCELO A. F. (2016)
ABSTRACT The damage control surgery, with emphasis on laparostomy, usually results in shrinkage of the aponeurosis and loss of the ability to close the abdominal wall, leading to the formation of ventral incisional hernias. Currently, various techniques offer greater chances of closing the abdominal cavity with less tension. Thus, this study aims to evaluate three temporary closure techniques of the abdominal cavity: the Vacuum-Assisted Closure Therapy - VAC, the Bogotá Bag and the Vacuum-pack. We conducted a systematic review of the literature, selecting 28 articles published in the last 20 years. The techniques of the bag Bogotá and Vacuum-pack had the advantage of easy access to the material in most centers and low cost, contrary to VAC, which, besides presenting high cost, is not available in most hospitals. On the other hand, the VAC technique was more effective in reducing stress at the edges of lesions, removing stagnant fluids and waste, in addition to acting at the cellular level by increasing proliferation and cell division rates, and showed the highest rates of primary closure of the abdominal cavity.